2017
DOI: 10.18632/oncotarget.20738
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long noncoding RNA Xist promotes proliferation of osteosarcoma by epigenetic silencing of P21

Abstract: Recent studies show that lncRNAs involve in the initiation and progression of various cancers including osteosarcoma (OS). IncRNA Xist has been verified as an oncogene in several human cancers, and its abnormal expression was closely associated with tumor initiation and progression. Nevertheless, the role of Xist in OS remains unclear. Here, we revealed the Xist expression level was up-regulated in OS tissues and discovered that Xist knockdown significantly repressed OS cell proliferation. Additionally, mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Recent studies demonstrated that XIST was associated with tumorigenesis, apoptosis, metastasis, and chemo‐ and radioresistance of cancers. Among them, XIST has been implicated to be upregulated in osteosarcoma (Gao et al, 2019; Lv, Miao, & Zhang, 2018; Li et al, 2019; Xu, Jiang, Fan, Gao, & Li, 2017; C. Yang et al, 2018), leading to the promotion of cell growth, migration, and invasion by targeting multiple signaling molecules. Our study demonstrated an oncogenic role of XIST in OS tumors and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that XIST was associated with tumorigenesis, apoptosis, metastasis, and chemo‐ and radioresistance of cancers. Among them, XIST has been implicated to be upregulated in osteosarcoma (Gao et al, 2019; Lv, Miao, & Zhang, 2018; Li et al, 2019; Xu, Jiang, Fan, Gao, & Li, 2017; C. Yang et al, 2018), leading to the promotion of cell growth, migration, and invasion by targeting multiple signaling molecules. Our study demonstrated an oncogenic role of XIST in OS tumors and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that some lncRNAs, including Xist, APTR, and ANCR, can recruit EZH2 to epigenetically silence the cdkn1a (cyclin-dependent kinase inhibitor 1A, p21) gene, thereby promoting cell proliferation (39)(40)(41). p21 is an important cell-cycle regulator that restrains the cell cycle by inhibiting CDKs in mouse embryonic fibroblasts (42,43).…”
Section: Syisl Ko In Mice Significantly Increases Muscle Fiber Densitmentioning
confidence: 99%
“…Lately, the binding relationship between long non-coding RNA (lncRNA) X-inactive specific transcript (XIST) and EZH2 in osteosarcoma has been proposed [14]. Identified as an oncogene, lncRNA XIST has been reported to be abnormally expressed in diverse cancers and related to tumor development and progression [15].…”
Section: Introductionmentioning
confidence: 99%